Computer-assisted implant placement and full-arch immediate loading with digitally prefabricated provisional prostheses without cast: a prospective pilot cohort study - Nikolay Makarov; Giorgio Pompa; Piero Papi (SpringerOpen, 2021)
Abstract Background Immediate loading of implant-supported full-arch rehabilitations has become routine practice when treating edentulous patients. The combination of static computer-aided implant surgery (s-CAIS) and digital prosthetic workflow could eliminate several treatment steps and facilitate prostheses delivery. The aim of this study is to evaluate the 1-year results of digitally prefabricated polymethyl methacrylate (PMMA) provisional prostheses without a cast for full-arch computer-assisted immediate loading. Materials and methods A digital pre-operative treatment planning was realized for all patients: dental implants and screw-retained abutments were selected in the planning software and two surgical templates were fabricated for each patient. The first template was mucosa or teeth-supported to drill the holes for fixating pins, while the second template was placed after raising a full-thickness flap and was supported by pins as well as soft or hard tissue distal support. Furthermore, based on the surgical planning, interim prostheses were digitally designed and milled of PMMA resin blocks with subsequent pink resin veneering. Osteotomies and implant placement were performed through the surgical guides and all implants were immediately loaded with prefabricated full-arch interim prostheses directly connected to titanium copings with a flowable resin. Results A total of 55 dental implants were placed in ten patients. In all cases, interim prostheses allowed the insertion of titanium copings without the need of access hole enlargement or adaptation. All the prostheses had 1 year of functional loading to simulate the long provisional phase. No screw loosening occurred at the first removal of the prostheses after implant osseointegration. No fracture occurred during the whole period. After 1 year, the mean marginal bone loss level was 0.37 ± 0.06 mm, while the implant survival rate was 98.18% (n=54/55), with just one implant failing but not affecting final prosthesis delivery to the patient. Conclusions Within the limitations of the present study, the authors concluded that digitally prefabricated provisional prostheses for full-arch immediate loading with s-CAIS could be a valid alternative treatment modality. Milled PMMA restorations proved to be durable enough during the long provisional phase, without prosthetic complications.